1993
DOI: 10.1021/bi00094a012
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde oxidoreductase activity in Desulfovibrio gigas: In vitro reconstitution of an electron-transfer chain from aldehydes to the production of molecular hydrogen

Abstract: The molybdenum [iron-sulfur] protein, first isolated from Desulfovibrio gigas by Moura et al. [Moura, J. J. G., Xavier, A. V., Bruschi, M., Le Gall, J., Hall, D. O., & Cammack, R. (1976) Biochem. Biophys. Res. Commun. 72, 782-789], was later shown to mediate the electronic flow from salicylaldehyde to a suitable electron acceptor, 2,6-dichlorophenolindophenol (DCPIP) [Turner, N., Barata, B., Bray, R. C., Deistung, J., LeGall, J., & Moura, J. J. G. (1987) Biochem. J. 243, 755-761]. The DCPIP-dependent aldehyde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
53
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 70 publications
(57 reference statements)
7
53
1
Order By: Relevance
“…These seemingly inconsistent results can be reconciled if the b2881 product oxidizes high intracellular levels of hypoxanthine and perhaps xanthine. This would not be surprising, since members of the xanthine oxidase family can have broad substrate specificies (3,11). In any case, our results do not conclusively define a function for this protein.…”
Section: Discussioncontrasting
confidence: 58%
“…These seemingly inconsistent results can be reconciled if the b2881 product oxidizes high intracellular levels of hypoxanthine and perhaps xanthine. This would not be surprising, since members of the xanthine oxidase family can have broad substrate specificies (3,11). In any case, our results do not conclusively define a function for this protein.…”
Section: Discussioncontrasting
confidence: 58%
“…gigas AOR was first described by Moura et al [68] and has been thought of as an aldehyde ''scavenger'', acting in a complex chain of electron-transfer proteins that links the oxidation of aldehydes to the reduction of protons [69]. The AOR-dependent nitrite reductase activity described herein could, therefore, constitute an alternative pathway to produce NO directly from aldehydes.…”
Section: Site Of Nitrite Reductionmentioning
confidence: 77%
“…However, its presence was suggested from spectroscopic studies (mainly electron paramagnetic resonance, EPR), which showed that most of the EPR properties of active DgAOR or AOR from Desulfovibrio desulfuricans ATCC 27774 (DdAOR) are similar to those of active XO [15,16]. In addition, cyanide acts as an inhibitor of DgAOR activity [17]; this is also the case in XO (where the cyanide is proposed to react with the sulfido ligand), and the desulfo form of DgAOR regains activity after resulfuration [18]. The position of the sulfido ligand in the active site has been debated; a crystal structure of ''resulfurated'' DgAOR crystals showed that the sulfido ligand introduced by adding an excess of sulfide ions was coordinated in the apical position to the molybdenum atom [19] (Fig.…”
Section: Introductionmentioning
confidence: 99%